Evaluation of the salivary level of glutathione reductase, catalase and free thiol in patients with oral lichen planus - Fahimeh Rezazadeh; Dorsa Mahdavi; Nima Fassihi; Hossein Sedarat; Elham Tayebi Khorami; Amir Tabesh (BMC, 2023)
Abstract Objective Oral lichen planus (OLP) is a usual chronic inflammatory disease of the oral mucosa with malignant capacity, whose pathogenesis is not yet well known. Free radicals and reactive oxygen species may have a vital role in the pathogenesis of oral lichen planus. This study aimed to assess Glutathione reductase, catalase, and free thiol levels in the saliva of OLP patients and compare it with healthy people. Methods In this cross-sectional study, 35 patients with OLP and 20 healthy people were involved. Five mL of whole, unstimulated saliva samples were collected in the morning, and the salivary levels of antioxidants were measured by ELISA technique. In this experiment, sex, age and OLP types were also evaluated. Results There was a significant decrease in the patients' salivary level of Glutathione reductase (0.2043 mU/ml in patients and 0.3901 mU/ml in the control group) and catalase (0.1525 mU/ml in patients and 0.2700 mU/ml in the control group) (p = 0.001). But there were no differences between the two groups regarding free-thiol levels (0.0586 mU/ml in patients and 0.0569 mU/ml in the control group) (p = 0.7). However, there was no correlation between age and gender with the antioxidants' contents. There was a significant decrease in glutathione reductase and catalase in the erosive type than in the non-erosive type. Conclusions In this study, we found that the salivary levels of Glutathione reductase and Catalase were lower in OLP patients than in the healthy group, which means these antioxidants were affected by OLP and also associated with the type of it. So salivary Glutathione reductase and Catalase levels may be used as biomarkers for OLP monitoring and treatment.